Núcleo aléfico: um estudo de A máquina do mundo repensada de Haroldo de Campos - Bomfim, Monalisa Medrado (2020)
This work proposes a critical analysis of the poem A máquina do mundo repensada, by Haroldo de Campos, published in 2000, composed in terza rima and structured in three cantos. The aim is to develop a reflection about the mystical and biblical elements present in Canto III, supported by literature theory, poetry criticism and the poet’s literary criticism, besides references about Kabbalah selected from the material available in the collection at Casa das Rosas: Centro de Referência Haroldo de Campos. The analysis starts from the hypothesis that the Aleph, letter and symbol from the jewish culture, is an image that moves rhizomatically in the poem, that is, it appears randomly along the poem. We intend to demonstrate with our reading that the alephic image dissimulates itself in other words, but it keeps exercising the symbolism inherent to the Aleph’s image. In this way, the objective of this work’s Chapter I is to recover the alephic images present in Canto III of the poem A máquina do mundo repensada (2004a). Chapter II aims to narrow the association between Haroldo de Campos and Kabbalah texts, circumscribing the work’s kabbalistic Universe. In order to do it, we focus on the analysis of the haroldian library books. The alephic nuclei located in Chapter I and the kabbalistic themes discussed in Chapter II guide the reading performed in Chapter III, in which Canto III of the poem A máquina do mundo repensada (2004a) is extensively analysed through Kabbalah bias. This analysis takes into consideration the theoretical apparatus of texts about Kabbalah and by Walter Benjamin (Infância berlinense: 1900 (2017) and Sobre o conceito de história (1987). Benjamin’s texts allow us to think about the relation between the poetic persona and the tradition, focusing on the Kabbalah tradition mobilized in the studied Canto.